2013
DOI: 10.1155/2013/760236
|View full text |Cite
|
Sign up to set email alerts
|

Heparanase Localization during Palatogenesis in Mice

Abstract: Palatogenesis is directed by epithelial-mesenchymal interactions and results partly from remodeling of the extracellular matrix (ECM) of the palatal shelves. Here, we assessed heparanase distribution in developing mouse palates. No heparanase was observed in the vertically oriented palatal shelves in early stages of palate formation. As palate formation progressed, the palatal shelves were reorganized and arranged horizontally above the tongue, and heparanase localized to the epithelial cells of these shelves.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…MMPs are sheddases that are capable of cleaving syndecans from the cell surface. Multiple studies have reported that MMP-1, -2, -3, -7, and -9 are involved with upregulation of HPSE in various cell lines (32,(39)(40)(41). Additionally, decreasing the levels of MMP-9 has been shown to ameliorate herpes simplex keratitis in vitro and in vivo (42,43).…”
Section: Resultsmentioning
confidence: 99%
“…MMPs are sheddases that are capable of cleaving syndecans from the cell surface. Multiple studies have reported that MMP-1, -2, -3, -7, and -9 are involved with upregulation of HPSE in various cell lines (32,(39)(40)(41). Additionally, decreasing the levels of MMP-9 has been shown to ameliorate herpes simplex keratitis in vitro and in vivo (42,43).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, Tgfβ-3-and Egfr-knockout mice, which display a cleft palate phenotype, have decreased or absent MMP expression in the MEE or MES (Miettinen et al, 1999;Blavier et al, 2001). Heparanase has also been detected in the MEE and MES and co-localized with MMPs -2, -3, and -9 (Hirata et al, 2013). MMP-25 can cleave only collagen IV and, in terms of substrates, displays more similarities to MMP-3 than other MT-MMPs (English et al, 2001).…”
Section: The Roles Of Mmps and Timps In Palatogenesismentioning
confidence: 99%
“…CSPGs, DSPGs, HSPGs, and HA are all enriched in developing palatal shelves [30][31][32][33]. The GAG chains, predominantly HA, which are accumulated in palatal mesenchyme and combined a large number of water molecules, are considered as the main driving force for palatal expansion and elevation.…”
Section: Introductionmentioning
confidence: 99%